Hormônios desreguladores endócrinos em matrizes ambientais - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2022)
This study aimed to analyze through a systematic literature review the presence in aquatic matrices of the natural hormones 17β-Estradiol (E2), Estrona (E1), in addition to the synthetic hormone present in contraceptive pills, 17α-Ethinilestradiol (EE2), considered endocrine disruptors DEs. Searches were conducted for peer-reviewed articles published from 2011 to 2021 that determined and quantitatively evaluated these hormones group in aquatic matrices, especially surface water and crude and treated wastewater. The results demonstrated that the most used extraction methodology is solid phase extraction (SPE) and for identification and quantification, are liquid chromatographic techniques (LC) and gas chromatographic techniques (CG) coupled to mass spectroscopy (DM). Estrona is the most abundant and often detected estrogen. Existing conventional effluent treatment systems are not able to remove concentrations of natural and synthetic hormones alone, requiring the junction of tertiary treatment, the presence of these hormones in treated effluent discharge sites. With regard to treatment technologies, activated sludge is the most widely used secondary treatment process. It was also observed that the incorporation of the advanced treatment process composed of anoxic-anaerobic membrane bioreactor, ultraviolet disinfection showed better results. The absence ofimplementation ofeffluent treatment plants also influences the incorporation ofEDs in the springs, so the implementation ofnew systems should be prioritized.
Keywords: Desreguladores endócrinos; Hormônios; Sistema de tratamento de esgoto; Ocorrência; Remoção; CNPQ::CIÊNCIAS DA SAÚDE::FARMÁCIA::TECNOLOGIA FARMACÊUTICA; Fisiologia ambiental